Effects of alcohol dependence on cortical thickness as determined by magnetic resonance imaging - Momenan, Reza; Steckler, Leah E.; Saad, Ziad S.; van Rafelghem, Stefanie; Kerich, Michael J.; Hommer, Daniel W. (Psychiatry research. Neuroimaging, 2012)
Alterations of brain structures have been seen in patients suffering from drug abuse or mental disorders like schizophrenia. Similar changes in volume of brain structures have been observed in both alcoholic men and women. We examined the thickness of gray matter in the cerebral cortex in control men and women (n=69, 47 men) and alcohol-dependent subjects (n=130, 83 men) to test the hypothesis that alcoholic inpatients would have more cortical damage than controls. We also hypothesized that alcoholic women would be more affected than alcoholic men. Alcoholic participants with a history of schizophrenia, psychotic, or bipolar disorder were excluded from the study. Volumetric structural magnetic resonance images were collected, 3D surfaces were created using Freesurfer, and statistical testing for cortical thickness differences was carried out using AFNI/SUMA. Covarying for age and years of education, we confirmed significant differences between alcoholics and healthy controls in cortical thickness in both the left and right hemispheres. Significant differences in cortical thickness between control men and women were also observed. These differences may reflect sexual dimorphisms in the human brain, a genetic predisposition to alcoholism and comorbid drug use, and the extent of gray matter damage in alcoholism and substance use.